Modelling the performance and emission prediction of RB211 aero-gas turbine engine fuelled by Jatropha-based biofuel - Azami, Muhammad Hanafi; Noorazman, Zahid; Savill, Mark; Li, Yi-Guang; Hilmi, Mohd Radzi (IOP Publishing, 2019)
Fossil fuel is one of the world vital energy resources. The development of transportation technologies increases the demand for petroleum derivative globally. Fossil fuel consumption produces emissions, which potentially harm the environment and human health. Many mitigations have been implemented to address the two main crises; the energy scarcity and environmental calamity. This paper will discuss on one of the potential solutions by analyzing the performance and emission prediction of aero-gas turbine engine fuelled by Jatropha-based biofuel. Performance analysis was made based on the thrust and specific fuel consumptions at different blended ratio percentages for various flight conditions. The three- shaft high-bypass-ratio engine model, which is identical to the Rolls Royce RB211-524 was used to model in an in-house Cranfield’s University software, PYTHIA. PYTHIA is integrated with the TURBOMATCH performance evaluation programme by iterating the mass and energy balance for each engine component. The analysis is then continued to predict Nitrogen Oxides emission index (EINOx) at every flight conditions using an in-house Cranfield’s University computer tool, HEPHAESTUS. HEPHAESTUS is an emission prediction software by using Zel’Dovich equations (for NOx) and models the emission by implementing a partially-stirred reactor (PSR) model and perfectly stirred reactor (PSRS) models at different zones in the combustor. Validation showed that HEPHAESTUS is able to capture a reasonable prediction as compared to the International Civil Aviation Organization (ICAO) databank. The performance the biofuel has shown an improvement in engine performance at higher percentage blended ratio but also increase the nitrous oxide indices emission slightly.